Globalization and Human Capital Formation - Fredrik Andersson; Kai A. Konrad (Institute for the Study of Labor (IZA), 2001)
This paper compares education investment in closed and open economies without government and with a benevolent government. The fact that the time consistency problem in taxation can make labor mobility beneficial even if governments are fully benevolent – which is known from other contexts – is shown to be true in the economies considered. It is further shown that labor mobility is unambiguously beneficial if private insurance for human capital investment is available.
Keywords: H21; H23; 330; Globalization; commitment; time consistent income taxation; migration; education effort; Bildungsinvestition; Offene Volkswirtschaft; Steuerpolitik; Zeitkonsistenz; Internationale Arbeitsmobilität; Globalisierung; Theorie